PHOSPHORUM SLAG AND PHOSPHOGYPSUM AS MAN-MADE INDUSTRIAL WASTE FOR CREATION OF MODIFIED FIRE AND EXPLOSION-SUPPRESSING POWDER COMPOSITIONS - Bayan Sapargaliyeva,; Aigul Naukenova,; Bakhyt Alipova, (Academic Scientific Journal of Chemistry, 2020)
One of the priority areas of life safety and environmental protection is the creation of modified fire and explosion-suppressing powder compositions using man-made waste from various industries. Their use makes it possible to reuse substandard (expired) fire extinguishing compositions, possibly as substances that slow down the processes of explosion and combustion of materials. Fire and explosion-suppressing powders at the end of the shelf life must be regenerated or disposed of. For the regeneration procedure, i.e. restoration of the fire-extinguishing properties of the powder, it is sent to the manufacturing plant to restore its properties and characteristics. This allows you to modify the properties of the powder and produce an improved product. At the same time, a significant contribution is made to the development of a system for the rational use of natural resources, disposal of production waste, preservation of the ecological situation in the area, as well as prevention of emergencies and emergencies at industrial dumps. Comprehensive and rational use of secondary material and raw materials and wastes of various industries should take a certain place in the raw material balance of industry and in the prevention of emergencies.